Building bridges or digging the trench? International organizations, social media, and polarized fragmentation - Matthias Ecker-Ehrhardt (University of Duisburg-Essen, Käte Hamburger Kolleg / Centre for Global Cooperation Research (KHK/GCR21), 2024)
Communication professionals working for International Organizations (IOs) are important intermediaries of global governance that increasingly use social media to reach out to citizens directly. Social media pose new challenges for IO public communication, such as a highly competitive economy of attention and the fragmentation of audiences driven by networked curation of content and selective exposure. In this context, IO social media communication has to make tough choices about what to communicate and how, aggravating inherent conflicts of IO communication between comprehensive public information (aiming at institutional transparency) - and partisan political advocacy (aiming at normative change). If IOs choose advocacy, they might garner substantial resonance on social media. IO advocacy nevertheless fails to the extent that it fosters the polarized fragmentation of networked communication and undermines the credibility of IO communication as a source of trust - worthy information across polarized 'echo chambers'. The paper illustrates this argument through a quantitative content and social network analysis of X/Twitter communication on the Global Compact for Safe, Orderly, and Regular Migration (GCM). Remarkably, instead of facilitating cross-cluster communication ('building bridges'), United Nations accounts seem to have substantially fostered ideological fragmentation ('digging the trench') by their way of partisan retweeting, mentioning, and (hash)tagging.
urn:nbn:de:hbz:465-20240705-072326-3
Keywords: 320; international organizations; social media; public communication; echo chambers; advocacy; United Nations; Global Compact for Migration; content analysis; supervised machine learning; social network analysis